Transformative communication technologies: the accountability challenge - Mansell, Robin (MATRIZes, 2019)
The paper broaches the causes and consequences of transformations in the media and communication technologies, discussing if those responsible for such transformations can be held to account for how the digitally mediated environment is changing. Older communication technologies also brought questions on accountability. However, today, new questions arise on the subject in relation to artificial intelligence, algorithms, big data and machine learning. In the face of possible harms and risks of digital innovation, it advocates that, in order to guarantee benefits for the citizens, a broad debate should be held, as well as researches able to support anticipatory policy measures.